Characteristics Of Youth Unemployment: Before And During The Covid-19 Pandemic In Indonesia - Cindy Aprilia; Yulia Anas (UNIVED Press, 2024)
This research aims to investigate the characteristics of young unemployment before and during the covid-19 pandemic in Indonesia, as well as to identify changes in the characteristics of young unemployment during this period. Young unemployment refers to individuals within the labor force, actively seeking employment, aged between 15 and 24 years, and not attending school. The study utilizes raw data from the Indonesian National Labor Force Survey (SAKERNAS) for the periods of August 2019 and 2020. To achieve these objectives, a binary logistic regression analysis with interaction effects is employed. The research findings indicate that young individuals within the labor force who are characterized as female, unmarried, have attained a minimum level of high school education, have not participated in any training, and possess work experience are more likely to experience unemployment before and during the covid-19 pandemic. Moreover, the occurrence of the covid-19 pandemic in 2020 has indeed had a significant impact on youth unemployment in Indonesia. The changes in the characteristics of youth unemployment during the pandemic are observed among young individuals within the labor force who are unmarried, have work experience, and reside in rural areas.